Synthesis of mixed Cu/Ce oxide nanoparticles by the oil-in-water microemulsion reaction method - Pemartin Biernath, Kelly; Vela González, Andrea; Moreno Trejo, Maira; Leyva Porras, César; Castañeda Reyna, Iván Eduardo; Juárez Ramírez, Isaías; Solans, Conxita; Sánchez Domínguez, Margarita (2016)
Cerium oxide and mixed Cu/Ce oxide nanoparticles were prepared by the oil-in-water (O/W) microemulsion reaction method in mild conditions. The Cu/Ce molar ratio was varied between 0/100 and 50/50. According to X-ray diffraction (XRD), below 30/70 Cu/Ce molar ratio, the materials presented a single phase consistent with cubic fluorite CeO2. However, above Cu/Ce molar ratio 30/70, an excess monoclinic CuO phase in coexistence with the predominant Cu/Ce mixed oxide was detected by XRD and High-Resolution Transmission Electron Microscopy (HRTEM). Raman spectroscopy showed that oxygen vacancies increased significantly as the Cu content was increased. Band gap (Eg) was investigated as a function of the Cu/Ce molar ratio, resulting in values from 2.91 eV for CeO2 to 2.32 eV for the mixed oxide with 30/70 Cu/Ce molar ratio. These results indicate that below 30/70 Cu/Ce molar ratio, Cu2+ is at least partially incorporated into the ceria lattice and very well dispersed in general. In addition, the photodegradation of Indigo Carmine dye under visible light irradiation was explored for selected samples; it was shown that these materials can remove such contaminants, either by adsorption and/or photodegradation. The results obtained will encourage investigation into the optical and photocatalytic properties of these mixed oxides, for widening their potential applications.